Proverbs 8,22-31: text, context, reception = Proverbios 8,22-31 : texto, contexto, recepción - Tomaselli, Davide (Filiación, 2024)
"The volume is dedicated to the study of the text, context and reception of Prov. 8:22-31 from its composition to the 5th century, a key passage in the history of theology of the first Christian centuries in order to explain the generation and identity of the Son of God and, particularly, in the so-called Arian controversy. ... [T]he reader is provided with a comprehensive insight into the development of the Trinitarian and Christological dogma of the first centuries, as well as of the history of Jewish and Christian exegesis. This volume expands and updates the study on Proverbs 8 carried out by Manlio Simonetti more than fifty years ago: it serves as a tribute to the great Italian scholar, who was a mentor to many disciples."--